Relationships between work-family and family-work conflicts and health of nurses - Buffering effects of social support - Łukasz Baka (Nofer Institute of Occupational Medicine, 2013)
Background: The aim of the study was to investigate the relationships between work-family conflict (WFC), family-work conflict (FWC) and health, as well as the moderating effect of social support. The study was based on the Job Demands-Resources model. Materials and Methods: There were 567 nurses from 21 Polish hospitals participating in the study. To verify the hypothesis four scales, which measured WFC, FWC, social support, physical complaints and job burnout, were used. Results: The results partially support the hypothesis. As predicted, high WFC and FWC were correlated with low physical (H1) and mental health (H2). Social support moderated negative effects of WFC (but not FWC) on mental health (H3). The effects of WFC and FWC on physical health were not moderated by social support (H4). Conclusion: The results also partially support the notion of the Job Demands-Resources model and provide further insight into processes leading to the high well-being of nurses in the workplace. Med Pr 2013;64(6):775-784